Ameliorating the Effect of Astragaloside IV on Learning and Memory Deficit after Chronic Cerebral Hypoperfusion in Rats - Sooyong Kim; Il-Hwan Kang; Jung-Bum Nam; Yoonchul Cho; Doo-Young Chung; Seung-Hwan Kim; Jeong-Soo Kim; Yong-Deok Cho; Eun-Ki Hong; Nak-Won Sohn; Jung-Won Shin (Molecules, 2015)
Astragaloside IV (AS-IV) has been reported to have a prominent antioxidant effect and was proposed as a promising agent for the prevention of neurodegenerative disorders accompanied by cognitive impairment. The present study investigated the ameliorating effect of AS-IV on learning and memory deficits induced by chronic cerebral hypoperfusion in rats. Rats were treated with two doses of AS-IV (10 and 20 mg/kg, i.p.) daily for 28 days starting from the 5th week after permanent bilateral common carotid artery occlusion. AS-IV treatment (at dose of 20 mg/kg) significantly improved the spatial learning and memory deficits assessed using the Morris water maze test in rats with chronic cerebral hypoperfusion. AS-IV significantly attenuated neuronal apoptosis as well as the levels of superoxide dismutase and lipid peroxidation markers, including malondialdehyde and 4-hydroxy-2-nonenal, in the hippocampus. AS-IV also significantly reduced 8-hydroxy-2’-deoxyguanosine expression, a maker of oxidative DNA damage, while significantly inhibited the astrocyte and microglia activation in the hippocampus. The results indicate that AS-IV has therapeutic potential for the prevention of dementia caused by cerebral hypoperfusion and suggest that the ameliorating effect of AS-IV on learning and memory deficits might be the result of suppressing neuronal apoptosis and oxidative damage in the hippocampus.